Learning from an analysis of closed malpractice litigation involving myocardial infarction. (May 2017) - Wu, Kuan-Han; Yen, Yung-Lin; Wu, Chien-Hung; Hwang, Chi-Yuan; Cheng, Shih-Yu
Abstract: Objective: To examine the epidemiologic data, identify the pattern of dispute, and determine clinical litigious errors by analyzing closed malpractice claims involving myocardial infarction (MI) in Taiwanese courts. Methods: A retrospective descriptive study was performed to analyze the verdicts pertaining to MI from the population-based database of the Taiwan judicial system between 2002 and 2013. The results of adjudication, involved specialists, primary dispute leading to lawsuits, and litigious errors were recorded. Results: A total of 36 closed malpractice claims involving MI were included. The mean interval between the incident and litigation closure was 65.5 ± 28.3 months. Nearly 20% of the cases were judged against clinicians and the mean payment was $100639 ± 49617, while the mean imprisonment sentence was 4.3 ± 1.8 months. Cardiologists and emergency physicians were involved in 56.3% of cases, but won 92.6% of lawsuits, while other specialists lost nearly 25% of lawsuits. The most common dispute was misdiagnosis (38.9%), but this dispute had the lowest percentage of loss (7.1%). Disputes regarding delayed diagnosis were judged against the defendants in 50% of claims. Clinicians lost the lawsuit in the following conditions: 1) misdiagnosis of MI in patients with typical chest pain and known coronary artery risk factors; 2) failure to perform thoughtful evaluation and series investigations in patients suspicious of ischemic heart disease; 3) failure to perform indicated treatment to avoid disease progression. Conclusions: Medical practitioners should keep a high index of MI suspicion, especially if the diagnosis and treatment of MI are beyond their daily practice. Prudent patient reevaluation, serial ECG and cardiac enzyme testing, and early consultation are suggested to reduce malpractice liability. Highlights: Medical practitioners should keep a high index of suspicion for MI. CV and EM won 92.6% of lawsuits, while other specialists lost about 25% of lawsuits. Nearly 40% disputes were misdiagnosis, but only 7.1% among them were loss lawsuits. Defandants lost 50% of claims in disputes regarding delayed diagnosis. Failure to perform patient re-evaluation can easily lead to malpractice liability.